(3JMaI GdCMHGH aj eGgjI GdfHGJ hGdCYTGHs
(3ChdgG (B:s
(3GddhHjG MH jDcd hjYjf Ydi GdLeGY eYQha HGdeZQH jRQY s
(3BNQgG (B:s
(3ef GdcJGH GdKGdK YfgG bhdg aUd aj ChLGY GdCSfGf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B162 - (3U(B174s
(3bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B45 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdWHs